The Plight of Teenage Girls Displaced by the COVID-19 Pandemic in Namibia A Critical Review - Hako, Anna Niitembu; Shikongo, Prisca Tautiko; Shanyanana-Amaambo, Rachel Ndinelao (European Scientific Journal, ESJ, 2023)
The phenomenon of teenage pregnancy has become a thorn in the flesh for many countries, including Namibia as many learners become pregnant while schooling. This study gives an exploratory analysis on the increased number of girls who were impregnated during lockdown. The key question of this paper is, what will happen to the future of these teenagers? Pregnancies among learners threaten, not only their human rights, but their health and social welfare and the health and welfare of the children born to them. These young females often terminate their education, and this has an implication for girls becoming uneducated and not being able to contribute to the socio-economic development of the country as their male counterparts. This practice may lead to a perpetual cycle of the culture of poverty in which their children may further go on to become a teenage parent. Therefore, this critical review paper focuses on four main areas; firstly, presents plight of teenage pregnancy displayed by COVID-19 in Namibia. Secondly, depicts the ideas of learner pregnancy policy, and life skills education guidelines. Thirdly, reveals factors influencing teenage pregnancy in schools in Namibia, (rape culture.) Fourthly, unpack the implications of learners’ teenage pregnancy (to human rights, health, socio-economic, psychological/mental health) to education, women and girls’ empowerment agenda and socio-economic development. Lastly, the article concludes by unveiling strategies to mitigate the scourge (the fresh ways of dealing) with the plight of teenage pregnancy in this transforming society and point out some areas for further studies. The answers provided by theoretical analysis are not always definitive in nature, however, they might provide some insight into future phenomena.